Estimating dynamic characteristic of lobou-lobou fault line (SMK Kundasang), Kundasang Sabah by microtremor measurements / Jamil Matarul … [et al.] - Matarul, Jamil; Ibrahim, Azmi; Hasbullah, Mohamad Amran (2012)
Kundasang was satisfied as seismic active area due to reactivation of Lobou-lobou fault zone (LFZ) and Mensaban fault zone MFZ11). These faults also contributed to widespread ground movements pose the main hazard in Kundasang areas especially SMK Kundasang [5]. Several studies have been conducted to rectify this problem including through letter methods in identifying faults, monitoring and observing geodynamic characteristic of SMK Kundasang [1]; [5]; [52]. However, actual causes of problem due to moderate active seismic area in Central North Zone Sabah are not yet revealed. Therefore, this study tries to reveal the problem based on dynamic characteristics by microtremor measurements. Microtremor measurement such as Ground Ambient Noise (GAN) and Refraction Survey (RS) is a very convenient tool to estimate the effect of surface geology on seismic motion without depending really on other geological information [3]; [34]; [35]; [38].